Negotiating EMI teacher identity in Japan’s internationalized classrooms: A duoethnography - Terashima, Alexandra V; Dalziel, Greg (Journal of International Students, 2026)
This duoethnographic study examines the experiences of two lecturers transitioning from English for Academic Purposes (EAP) to English-Medium Instruction (EMI) at a Japanese university, where they teach mixed cohorts of degree-seeking students and short-term exchange students. Through collaborative dialog, we explore how teaching in diverse pedagogical contexts, coupled with conflicting student expectations, shapes professional identity and teacher practice. Our analysis identifies three tensions: divergent interpretations of whether EMI should prioritize content or intercultural exchange; mismatched expectations between degree-seeking students wanting language practice and exchange students with varying levels of academic engagement; and identity disruption as confident EAP instructors became uncertain EMI teachers. We argue that inclusive internationalized classrooms require recognizing the emotional labor and identity work of faculty.